2011
DOI: 10.1007/s00415-011-6097-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity in Parkinson’s disease

Abstract: Patients with Parkinson’s disease (PD) are likely to become physically inactive, because of their motor, mental, and emotional symptoms. However, specific studies on physical activity in PD are scarce, and results are conflicting. Here, we quantified daily physical activities in a large cohort of PD patients and another large cohort of matched controls. Moreover, we investigated the influence of disease-related factors on daily physical activities in PD patients. Daily physical activity data of PD patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
188
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 286 publications
(223 citation statements)
references
References 42 publications
7
188
0
8
Order By: Relevance
“…Instead, walking behavior in everyday life can be measured using accelerometers, which are wearable devices measuring body acceleration during a specific wear‐time period (Matthews, Hagstromer, Pober, & Bowles, 2012). Measuring walking in everyday life is especially relevant in PD as this group are less physically active than people without the disease (van Nimwegen et al., 2011). While such objective gait assessments provide important information, they are not feasible in most clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, walking behavior in everyday life can be measured using accelerometers, which are wearable devices measuring body acceleration during a specific wear‐time period (Matthews, Hagstromer, Pober, & Bowles, 2012). Measuring walking in everyday life is especially relevant in PD as this group are less physically active than people without the disease (van Nimwegen et al., 2011). While such objective gait assessments provide important information, they are not feasible in most clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies have explained only up to 28% of the variance of the level of physical activity of these individuals 2,5 . Knowledge of the factors that affect the level of physical activity of individuals with PD may guide clinicians that work with PD rehabilitation, and thereby prevent inactivity and its consequences.…”
Section: Main Determinants Of Physical Activity Levels In Individualsmentioning
confidence: 83%
“…A recent study indicated that individuals with PD are 29% less active than healthy individuals 2 . However, the ability of patients in the initial phase of PD to perform physical exercise may be comparable to that of healthy individuals when they maintain a certain level of regular physical activity.…”
Section: Main Determinants Of Physical Activity Levels In Individualsmentioning
confidence: 99%
See 2 more Smart Citations